The high frequency firm survey 'Bundesbank Online Panel-Firms' - Dominik Boddin; Mona Köhler (Journal of Economics and Statistics, 2024)
The Bundesbank Online Panel - Firms ('BOP-F') is a dataset with responses from a high frequency firm-level survey of the same name. The Bundesbank has conducted the survey since June 2020, and since July 2021 the survey has been carried out at a monthly frequency. Every month, around 3000 firms from all economic sectors, regions and size classes are surveyed. The survey consists of recurring core questions about the economic situation of firms and their expectations and special questions that usually differ from quarter to quarter. The latter often relate to current topics, for instance, climate change, digitalization, Covid-19. The data can be accessed for research and especially the possibility to combine it with other administrative Bundesbank data makes it particularly valuable for research. The objective of this paper is to describe the methodology of the data collection, the content data as well as the data's research potential.
Keywords: C81; C83; G30; M21; 330; corporate finance; COVID-19 pandemic; establishment survey; firm decisions; labor market; survey methodology